Impact of environmental policies, regulations, technologies, and renewable energy on environmental sustainability in China’s textile and fashion industry - Bibi, Sughra; Khan, Asif; Fubing, Xue; Jianfeng, Hu; Hussain, Saddam; Khan, Arshad Nawaz (Frontiers in Environmental Science, 2024)
In this study, we bridge a crucial gap in the literature by investigating the interplay between environmental regulations, technological innovations, and renewable energy adoption and their impact on sector-specific environmental performance in the textile and fashion industry. Leveraging time series data from 1995 Q1 to 2022 Q4 and using autoregressive distributed lag (ARDL) and Granger causality techniques, this research is built upon the environmental Kuznets curve (EKC) hypothesis and regulatory push innovation hypothesis to unravel these complex interactions. Our findings demonstrate that rigorous environmental regulations and taxes are pivotal in enhancing environmental outcomes across various industry sectors, leading to significant reductions in greenhouse gas emissions and particulate matter. However, the total leather and feather production (LFP) and total fashion production (FP) sectors are highly responsive to environmental policy and regulations. Although technological advancements and research and development (R&D) initially increase ecological footprints due to high upfront costs, they are indispensable for achieving long-term environmental improvements and reshaping regulatory landscapes. The adoption of renewable energy sources, meanwhile, delivers immediate and substantial reductions in carbon emissions, highlighting their critical role in advancing industry sustainability. In this study, we advocate for leveraging environmental regulations as drivers of technological innovation and sustainability, urging policymakers to implement incentives for technological progress and renewable energy adoption. The implications of this research are significant for both industry stakeholders and policymakers. By positioning environmental regulations as catalysts for technological advancement, in this study, we emphasize the importance of a proactive, integrated approach to sustainability. Despite the study’s regional focus, which may limit generalizability, future research should include longitudinal and comparative analyses across varied regions and emerging technologies to refine strategies for superior environmental performance.